Control of high blood pressure by Acupuncture In subjects with essential hypertension - Hazim k. Abbas; Isra’a F. Ja’afar; Basil N. Saeed (مجلة كلية الطب, 2012)
advancing age. The risk of cardiovascular disease in adults is lowest with systolic BP <120 mm Hg and diastolic BP < 80 mm Hg and increases progressively with higher systolic and diastolic blood pressures. Acupuncture (from the Latin word acus, “needle”, and pungere, meaning “prick”) is a technique in which the practitioner inserts fine needles into specific points on the patient’s body. Accupuncture could be used as a nonpharmacological way of controlling high readings of blood pressure among cases with essential hypertension. This study aimed to investigate the effects of acupuncture on essential hypertension. Patients and Methods: 51 hypertensive patients of both genders and 30 normotensive control subjects were involved in the study during the period from 1 December 2010 to 28 Feb 2011. Each subject recieved needling technique at certain acupoints of the body meridians according to Chinese medicine theory for 10 sessions, each session was thirty minutes and the responses were followed up for three months from the last session. Points selected are known as followed in Chinese medicine as ( du 20 , liver 3 and large intestine 11). Results : Patient group which consists of (51) individuals{ (37) males and (14) females}, from those 51, there were 39 with response i.e they became normotensive and this represent (76.47%) while the rest were still hypertensive (23.52%) but they showed significant change in all parameters after treatment Conclusion: From this study we conclude that acupuncture decreases blood pressure in hypertensive patients and had no hypotensive effect on normal subjects involved in this study.